Infections in immunosuppressed travellers with autoimmune inflammatory diseases—a narrative review and advice for clinical practice. (22nd May 2021) - Allen, Victoria; Longley, Nicky
Abstract: The management of autoimmune, inflammatory diseases has been revolutionized by biologic therapies. A beneficial consequence of better disease control is that more patients are well enough to travel the world. There is now a class of traveller, the significantly immunosuppressed person with autoimmune disease, with specific risks and requirements. This review introduces the concept of the pre-travel risk assessment and discusses the major vaccine-preventable and non-vaccine-preventable travel-associated infections. The challenges and controversies around vaccination and immunosuppression are reviewed with advice for clinical practice.